Supply Chain Innovation Effects on Supply Chain Efficiency in Teak Furniture Industry at Phrae Province - Yotapakdee, Teeka; Kiratikarnkul, Siriporn; Howpinjai, Itsaree; Sukjaroen, Siriluk; Wanichdilokrat, Thiti; Wirojanarome, Wanwasa; Kamton, Ratchaneewan; Asanok, Lamthai (Journal of Business, Innovation and Sustainability (JBIS), 2022)
The purpose of the research was to study the innovation affects the supply chain efficiency and developed the highest efficiency of supply chain innovation in the teak furniture industry. As a result, chain 1 timber processing used operation innovation about wood defect classification of wood processing. Efficiency was benefiting 1,637.19 THB/m3 and ROI 63.90%. Chain 2 making products used operation innovation about wood drying, increasing fire retardant of wood and designing innovation then efficiency was benefiting 3,293.43 THB/m3 and ROI 18.81%. Chain 3 repairing used operation innovation about changing step of polish and painting. Efficiency was benefiting 2,009.95 THB/m3 and ROI 45.78%. Chain 4 marketing used operation innovation about transportation service with a painter that efficiency was the reliability of entrepreneurs who can advantage of competitors. Chain 5 consumers got designing innovation that efficiency was consumers’ purchase decision of teak products. Therefore, the development of supply chain innovation can improve the teak industry. As the model consists in quality control development, research, and development, value added product and marketing development that important for entrepreneurs who can advantage of competitors of business.